Moby Dick : or, The whale - Melville, Herman, 1819-1891.; Fadiman, Clifton, 1904-1952.; Robinson, Boardman, 1876-1952. (Norwalk, Conn. : Easton Press, 1977)
Consumed by an insane rage, Captain Ahab has but one purpose in life-- revenge on the great white whale who maimed and disfigured him.
Keywords: Ahab, -- Captain (Fictitious character) -- Fiction; Whales -- Fiction; Whaling -- Fiction